The Efforts of Bem Fkip University of Labuhanbatu in Developing Leadership Character In 2021 - Muhammad Andre Syahputra; Panggih Nur Adi (Budapest International Research and Critics University, 2022)
This study aims to see the results of the performance of the Bem Fkip Labuhanbatu University in developing the leadership character of the Chair and administrators of the Bem Fkip Labuhanbatu University in carrying out daily activities in the campus environment during the tenure and management of the past year. This research method uses descriptive qualitative research methods. This research conducted inSM road. Raja Aek Tapa no 162AKM 35 Rantauprapat. This instrument uses a questionnaire. The results of this study based on data analysis; it was found that the management of Fkip Labuhanbatu University 100% showed a disciplined attitude while being the administrator of the Bem Fkip Labuhanbatu University. An ideal leader must be honest, responsible, independent, creative, and disciplined so that he will be able to be open to his members in all policies taken. A leader who has an honest, responsible, independent, creative and disciplined nature will definitely make all administrators believe in all his words and actions. Will be quickly followed and implemented by all members of the organization.